The Correlation Between Temperament and Fitness for Work According to the Persian Medicine Viewpoints: Persian Medicine Viewpoints on Fitness for Work: Persian Medicine Viewpoints on Fitness for Work - Mazhari, Mohammad Mahdi; Shams Ardekani, Mohammad Reza; Karimi, Mehrdad; Ayati, Mohammad Hossein; Mohammadi, Saber (Galen Medical Journal, 2023)
Working is an inseparable part of a human being’s life, every person must have a job to earn a living. However, working comes at a physical and mental cost not only to the working person but also to his/her co-workers and employers, and could also affect the environment. Therefore, each potential employee must be assessed to see if they are suitable for the job and vice versa. In occupational medicine, fitness for work is now determined by clinical and paraclinical testing, which is seen as a useful procedure, yet illnesses and accidents still happen at work. This procedure could be facilitated and enhanced by a more all-encompassing strategy, such as the temperamental theory in Persian medicine. Through temperamental theory, each person is assessed based on specific signs and symptoms according to the qualities of hotness-coldness, and wetness-dryness which can provide extra insights into an employee’s capabilities. This study aims to provide specific characteristics of each temperament, and their relationship with personal traits that could affect job performance, as well as job suggestions for each temperament through an extensive review of Persian medicine books and matching them with the current occupational medicine resources.